MEDIA BUKU SAKU DAN PENYULUHAN TERHADAP PENGETAHUAN REMAJA TENTANG HIV/AIDS DI SMK NEGERI 2 JAYAPURA - Flora Niu; Yeni Wardhani (GEMA KESEHATAN, 2021)
HIV/AIDS is a public health problem that requires serious attention because it attacks the human immune system, which can cause death. One of the causes of the spread of HIV infection due to unsafe sex. Based on WHO data in 2019, 78% of new HIV infections in the Asia Pacific region. The highest AIDS case for the last eleven years was in 2013, 12,214. HIV AIDS cases in Indonesia in 2019 reached 50,282 points, an increase of around 7.78% compared to the previous year. Jayapura City is one of the cities in Papua and ranks second in this case after Nabire Regency. As for the number of people with HIV, 1,978 and AIDS sufferers, 4,213 and 185 people have died. HIV transmission occurs at the productive age. The purpose of the study was to find out the knowledge of adolescents about HIV/AIDS through pocketbooks and counseling. The research method is a quasi-experimental research design with Pretest-Postest Design with Control group. The number of respondents was 30 students, namely students of class X vocational high school two Jayapura City. The way of taking respondents is purposive sampling. This study used pocketbook media as the treatment group and HIV/AIDS counseling as the control group. This study used a questionnaire with a pre-post-test-analysis using an independent test. The results showed a difference between pocketbook media and counseling on adolescent knowledge about HIV/AIDS with a p-value of 0.00. In conclusion, there is a significant difference in ability between pocketbook media and counseling.